Integrated Situational Analysis of Chronic Energy Deficiency to Inform A Community-Based Mentoring Model in Indonesia - Moch Taufik Hidayatullah; Sri Achadi Nugraheni; Bagoes Widjanarko; Apoina Kartini (Jurnal Kesehatan Masyarakat, 2026)
Maternal malnutrition in Central Lombok remains a challenge. This study aimed to identify multilevel determinants of chronic energy deficiency among pregnant women through an integrated situational analysis using a mixed-methods approach to inform a community-based mentoring model in Indonesia. A sequential exploratory mixedmethods design was conducted in 2025 at the district health office and five community health centers. The qualitative phase used purposive sampling of stakeholders and cadres, while the quantitative phase included 206 pregnant women with mid-upper arm circumference (MUAC) <23.5 cm selected through cluster random sampling. The dependent variable was MUAC status, with independent variables including maternal characteristics, dietary intake, food taboos, antenatal care (ANC), iron–folate supplementation, mentoring exposure, knowledge, and attitudes. Data were analyzed using contingency coefficients and multiple logistic regression. Food taboos were reported by 43.2% and were significantly associated with MUAC (p=0.023). Energy and protein inadequacy were 91.3% and 84.0%, respectively. ANC attendance (94.7%) and iron–folate use (91.3%) were high. High-risk maternal age increased the odds of lower  MUAC (OR=2.364; 95% CI:1.208–4.629), while higher education decreased the odds (OR=0.528; 95% CI:0.279–0.998). Mentoring exposure (OR=2.636; 95% CI:1.238–5.612) and parity (OR=1.610; 95% CI:1.122–2.310) were also significant. These findings inform community-based mentoring models focusing on dietary behavior and social context.